AN APPLICATION OF THE FIVE PRECEPTS TO ENCOURAGE OF PEACEFUL COEXISTENCE OF ETHNIC GROUPS IN THE WESTERN - Bhuriwatdhako, Phramaha Kriengsak; Phrapidokkosol; Phrarajwallapajan; ๋Jotipuñño, Phramahaprakob; Phrakhrupramotepanyawat; Nanavipulo, Phrakhrudhammatonphaiboon; Phrakhrusamutwachiranuwat; Phasukko, Phrakhrusamuworravit; Jayadatto, Phrakhrusangharaksongphan; Srilert, Nattanat (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research article were 1) to study the application of the Pañca-sĩla or the Five Precepts in the daily life of ethnic groups in the Western, and 2) to analyze the model of the application of the Pañca-sĩla or the Five Precepts to encourage the peaceful coexistence of ethnic groups in the Western. This research was a qualitative research using In-depth interview with 8 key informants included government heads, community leaders and village scholars in western area of Thailand according to the characteristics of the appropriate group representation from a specific randomization method then analyzed the data obtained by means of content analysis and trying to keep the original and using a group discussion with 8 qualified persons including heads of government agencies, community leaders and religious scholars from the random sampling, the data obtained by analyzing descriptive content. The findings of this research were following: 1) The application of the Pañca-sĩla or the Five Precepts in the daily life of ethnic groups in the Western has 5 elements, there are life insurance, property insurance, family insurance, social insurance, health insurance. 2) The model of the application of the Pañca-sĩla or the Five Precepts to encourage the peaceful coexistence of ethnic groups in the Western found that there was continuous promotion of reconciliation through various public spiritual activities due to the fact that at present all sectors were working together and driving the Five Precepts Village Project according to the 20-year National Strategy by emphasizing on the participation process of 3 coordination or Pavara principle (Families-Temples-Government/Schools), family institute, Buddhist institute and administrative institutions and educational institutions were coordinated as network called “ Good conduct in Buddhist way network” which conducted social activities using the Five Precepts Village Project as a base.